(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Getting married is one the key dream of young men at the age of maturity. The aim is getting a trustworthy partner to live together in good and worse moments. But living together often allow you to discover some strange faces of your partner. This may either be bitter, illusive or regretful or the opposite. The purpose of this paper is the show how important love is in life is and the necessity for both men and women to be truthful. To reach our goal, we essentially went through documentary research and have used Marxist Criticism, literary criticism as literary theory. At the end of our study we come to the conclusion that loving is good but being sincere and truthful in love is the best. The most important is what each partner is doing to keep the flame of love in permanently lit the house.